Perancangan Hybrid Mobile Application Penghubung Orang tua dan Guru pada Sekolah Taman Kanak-Kanak - Charlene Alicia Wagiu; Yulianus Palopak (TeIKa, 2019)
Parents and teachers are the main figures in the education of school-age children. In school, teachers play a role in educating students, but outside of school parents are responsible to nurture their children. Therefore communication between parents and teachers is very important. In fact, there are many barriers in communication between teachers and parents. Busyness and time limitedness are the biggest problem. There is a need for a system that can facilitate communication activity betweenteachers and parents. This research builds an application that facilitates communication between teachers and parents using hybrid mobile technology. Mobile hybrid technology was chosen because it can be a solution for application development that can be used on various platforms available on smartphones such as Android, iOS and Windows. The method used in the development of this system is SDLC (System Development Life Cycle) with the waterfall model with the stages of analysis, design, implementation and maintenance of the system. The results of this design are in the form of an application that can be used on various smartphone platforms, which can facilitate communication activity between teachers and parents. Key words: Hybrid mobile, school application